CSR EXPENDITURE AND FINANCIAL PERFORMANCE: A SYSTEMATIC REVIEW OF SLACK RESOURCES AS A MODERATING VARIABLE THROUGH THE LENS OF AGENCY THEORY AND SLACK RESOURCE THEORY - Ika Prayanthi; Danny Rantung; Nouke Rantung (Asosiasi Dosen Muda Indonesia, 2026)
The question of whether corporate social responsibility (CSR) expenditure helps or hurts firm financial performance has generated decades of research without producing a settled answer. This systematic narrative review examines 50 peer-reviewed studies published between 1963 and 2026, with an emphasis on Scopus-indexed empirical work from 2020 onward, to map what the literature shows about this relationship and why the evidence points in so many directions. Two theoretical frameworks organise the analysis: agency theory (Jensen & Meckling, 1976) and slack resource theory (Bourgeois, 1981). The review finds that the CSR-financial performance relationship is positive on average but conditional in important ways. Unabsorbed slack, meaning liquid discretionary resources, consistently strengthens the positive relationship because it allows firms to fund CSR without reducing operational efficiency and because markets read such investment as a credible signal of financial health. Absorbed slack, by contrast, shows a non-linear pattern: modest levels appear to support CSR-linked performance gains, while high levels tend to invite the managerial opportunism that agency theory predicts. Governance quality emerges as the factor that determines which of these two forces wins out. Five research gaps are identified, covering measurement standardisation, the distinction between mandatory and voluntary CSR, causal identification, optimal slack thresholds, and the shortage of evidence from developing economies outside China.